Histological and Physiological Study: The Effect of Testosterone On The Reproductive System In Male Albino Rats - Al-Hakeem, Aaya Hamid (Medical Science Journal for Advance Research, 2026)
Objective: The present research was done to explore the consequences of testosterone on fertility parameters in male albibno rats by investigating the histological and physiological alterations of the male reproductive system of rats that were orally dosed with testosterone for 8 weeks. Methods: They were mature, healthy and sexually mature, aged between 8-9 weeks, obtained from the College of Sciences University of Kufa. Their weights were between 300-250 g. The animals were placed inside special plastic cages and these were sprayed Cages with sawdust periodically. The cages were taken care of, mattresses were changed and sterilized with disinfectants every three days. The animals were housed in a special air-conditioned room. The animal house was equipped with an air vacuum, thermostat and an oil heater that could control the temperature between 22-25 degrees Celsius, as well as controlling the daily lighting period of 14 hours. Almost laboratory animals were given free diet and drinking water throughout the study period There were rats left in order to prepare for two weeks before starting the experiment. There were two groups of creatures: treated with testosterone group and control group. Then Animals are sacrificed by injecting them with a mixture of xylene and ketamine immediately after their death. We make an incision in the abdominal cavity in the shape of a letter T after that the genitals are lifted ,the testicles and the right epididymis are cut, the fatty tissue is removed from around the testicles and the right testicle is placed on a filter paper and weighed by an electronic scale . Then it is transferred to ethylene alcohol at a concentration of 70% for preservation , after which it is subjected to a microscopic examination to study the tissues. blood collected in anticoagulant ADTA ) tubes2-3ml), to measured of LH , FSH and Testosterone level hormone. Results: Histopathological analysis of the testes showed decreased changes in the scorpion ducts (p<0.001). LH and FSH levels of the study group were (p<0.05) compared to the control and sham groups. Conclusion: Treatment of male albino rats with testosterone at different doses (100, 200 mg/kg) for 60 days resulted in significant reductions in body weight and penis size. Male rats were given different doses of testosterone (100, 200 mg/kg) for 60 days.Testosterone decreased testosterone. arone and reduces follicle-stimulating hormone and luteinizing hormone levels. When male rats were given different doses of testosterone (100 and 200 mg/kg) for 60 days, testosterone-related changes in the testes were observed. The prostate, epididymis, and intercellular spaces formed as a result of albino rat testosterone have a negative effect on male fertility.